Pengembangan Media Audio Visual dalam Pembelajaran Bahasa Inggris Siswa Kelas II MI Al-Hikmah 1 Sepatan - Rosnaningsih, Asih; Siti Nur’alfiah; Nazifah, Ismiatun; Hukmah, Fakah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to develop an audio-visual media product in the form of learning videos to improve the quality of learning activities, especially in English subjects in grade II Elementary School. With learning media, the teaching and learning process becomes easier and more interesting, so that students can understand the subject matter easily, the learning efficiency of students can also increase because it is in accordance with the planned learning objectives. This research is a type of Research and Development (R&D) research with the ADDIE model development framework. Based on the results of the questionnaire, a score of 80% was obtained, so it can be concluded that this audio-visual media is ‘very good’ for improving the quality of class II English subjects at MI Al-Hikmah 1 Sepatan.